One-pot synthesis of gold nanoparticle/molybdenum cluster/graphene oxide nanocomposite and its photocatalytic activity - Barras, Alexandre; Das, Manash R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Cordier, Stephane; Szunerits, Sabine; Boukherroub, Rabah (Applied Catalysis B-Environmental, 2013)
The paper reports on a facile one-pot synthesis of a tri-component gold nanoparticle/molybdenum cluster/graphene oxide (AuNPs@Mo-GO) nanohybrid composite. The synthetic methodology consists on direct UV irradiation of an aqueous solution containing graphene oxide (GO), Na-2[Mo6Br8(N-3)(6)], HAuCl4 center dot 3H(2)O and isopropanol at room temperature in air using a UV fiber lamp. The composite material exhibits very high photocatalytic activity for the degradation of rhodamine B under visible light irradation. The resulting nanohybrid material was characterized using Raman spectroscopy, UV-vis spectrometry, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). (c) 2012 Elsevier B.V. All rights reserved.
Keywords: gold nanoparticles; graphene oxide; Nanohybrid; Photodegradation; Rhodamine B; visible light; [Mo6Br8(N-3)(6)](2-)cluster

On demand electrochemical release of drugs from porous reduced graphene oxide modified flexible electrodes - Boulahneche, Samia; Jijie, Roxana; Barras, Alexandre; Chekin, Fereshteh; Singh, Santosh K.; Bouckaert, Julie; Medjram, Mohamed Salah; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
Despite the advantages of an electrochemical control for drug release, only a handful of electrochemical-based release systems have been developed so far. We report herein on the development of an electrochemically activatable platform for on-demand delivery of drugs. It is based on flexible gold thin film electrodes coated with porous reduced graphene oxide (prGO) nanosheets onto which the drug of interest has been integrated beforehand. Two different drugs are investigated here: ondansetron hydrochloride (ODS), a selective 5-HT3 receptor antagonist used for preventing nausea and vomiting caused by chemotherapy and radiotherapy, and ampicillin (AMP), an antibiotic to prevent and treat a number of bacterial infections such as respiratory tract infections, urinary tract infections, and meningitis. In the case of ODS, application of a negative potential bias of -0.8 V results in a sustained slow ODS release with an ODS flux of 47 mu g cm(-2) h(-1). In the case of AMP, we show that polyethyleneimine modified prGO (prGO/PEI) is an extremely efficient matrix. Upon the application of +0.8 V, 24% of AMP could be released from the electrical interface in a time span of 2 h. The released AMP kept its antibacterial activity as demonstrated by antimicrobial tests. These examples illustrate the major benefits of the developed approach for biomedical applications.

Magnetic reduced graphene oxide loaded hydrogels: highly versatile and efficient adsorbents for dyes and selective Cr(VI) ions removal - Halouane, Fatima; Oz, Yavuz; Meziane, Dalila; Barras, Alexandre; Juraszek, Jean; Singh, Santosh K.; Kurungot, Sreekumar; Shaw, Pankaj K.; Sanyal, Rana; Boukherroub, Rabah; Sanyal, Amitav; Szunerits, Sabine (Journal of Colloid and Interface Science, 2017)
The formation of composites of reduced graphene oxide (rGO) and magnetic nanoparticles (MP) has flourished in recent years as they combine the advantages of both nanomaterials. Most of these composite materials are prepared by in situ formation of MP onto rGO or by the post-adsorption onto rGO. We report here on a simple and highly controlled method for the fabrication of different magnetic 3D rGO-loaded hydrogels. Cellulose bound magnetic nanoparticles (MP@cellulose) were synthesized by chemical co-precipitation and loaded together with rGO into poly(ethylene glycol) dimethacrylate based hydrogels during their fabrication using photo-polymerization. The magnetic rGO-loaded hydrogels proved to be highly adaptable to different applications. The as-formed composites allowed for efficient dye removal with an adsorption capacity of 111.9 +/- 4 mg g(-1) in the case of methylene blue (MB). Integration of poly(ethyleneimine) (PEI) allowed for the selective capturing of Cr6+ ions with an adsorption capacity of 313 12 mg g-1. Most importantly, independent of the application, the magnetic rGO-loaded hydrogel can be regenerated without loss of its adsorption capacity. (C) 2017 Elsevier Inc. All rights reserved.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.

Enhanced electrocatalytic activity of PtRu/nitrogen and sulphur co-doped crumbled graphene in acid and alkaline media - Pang, Liuqing; Miao, Yuanyuan; Bhange, Siddheshwar N.; Barras, Alexandre; Addad, Ahmed; Roussel, Pascal; Amin, Mohammed A.; Kurungot, Sreekumar; Szunerits, Sabine; Boukherroub, Rabah (Journal of Colloid and Interface Science, 2021)
The low mass activity and high price of pure platinum (Pt)-based catalysts predominantly limit their large-scale utilization in electrocatalysis. Therefore, the reduction of Pt amount while preserving the electrocatalytic efficiency represents a viable alternative. In this work, we prepared new PtRu2 nanoparticles supported on sulphur and nitrogen co-doped crumbled graphene with trace amounts of iron (PtRu2/PF) electrocatalysts. The PtRu2/PF catalysts exhibited enhanced electrocatalytic performance and stability for the hydrogen evolution reaction (HER) at pH = 0. Moreover, the prepared PtRu2/PF electrocatalyst displayed higher HER activity than commercial 20% Pt/C. The PtRu2/PF catalyst achieved a current density of 10 mA cm(-2) at an overpotential value of only 22 mV for HER, performing better activity than many other Pt-based electrocatalysts. Besides, the PtRu2/PF revealed a good performance for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. The PtRu2/PF catalyst recorded a current density of 10 mA cm(-2) at an overpotential of only 270 mV for OER in KOH (1.0 M) solution and an onset potential of 0.96 V vs. RHE (at 1 mA cm(-2)) for ORR in KOH (0.1 M) solution. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: HER; OER; ORR; PtRu2; Sulphur and nitrogen co-doped crumbled graphene